PV module maximum power point tracker (MPPT) using microcontroller - Nadiathul Raihana, Ismail (2008)
PV Module Maximum Power Point Tracker(MPPT) , is a photovoltaic system that uses the photovoltaic array as a source of electrical power supply. Every photovoltaic (PV) array has an optimum operating point, called the maximum power point, which varies depending on cell temperature, the insolation level and array voltage. The function of MPPT is needed to operate the PV array at its maximum power point. The design of a Maximum Peak Power Tracking (MPPT) is proposed utilizing a boost-converter topology. Solar panel voltage and current are continuously monitored by a closed-loop microprocessor based control system, and the duty cycle of the boost converter continuously adjusted to extract maximum power. The design consists of a PV array, DC-DC Boost converters (also known as step-up converters) and a control section that uses the PIC16F877A microcontroller. The control section obtains the information from the PV array through microcontroller’s Analog to Digital Converter (ADC) ports and hence to perform )the pulse width modulation (PWM) to the converter through its Digital to Analog Converter (DAC) ports. Many such algorithms have been proposed. However, one particular algorithm, the perturb-and-observe (P&O) method, claimed by many in the literature to be inferior to others, continues to be by far the most widely used method in commercial PV MPPT’s.